2009
DOI: 10.1007/s12275-009-0194-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional shifts in unvegetated, perhumid, recently-deglaciated soils do not correlate with shifts in soil bacterial community composition

Abstract: Past work in recently deglaciated soils demonstrates that microbial communities undergo shifts prior to plant colonization. To date, most studies have focused on relatively 'long' chronosequences with the ability to sample plant-free sites over at least 50 years of development. However, some recently deglaciated soils feature rapid plant colonization and questions remain about the relative rate of change in the microbial community in the unvegetated soils of these chronosequences. Thus, we investigated the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 54 publications
5
65
0
Order By: Relevance
“…This interpretation is corroborated by the observations that distance from the terminus is represented by a vector opposite to those representing the other two variables in the redundancy analysis plot (Figure 3). The results from the multivariate analysis therefore suggest that glacier debris cover may host chronosequences similar to those observed in glacier forefields Nicol et al, 2005;Nemergut et al, 2007;Schmidt et al, 2008;Sattin et al, 2009;Schutte et al, 2009Schutte et al, , 2010Philippot et al, 2011;Knelman et al, 2012;Zumsteg et al, 2012).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…This interpretation is corroborated by the observations that distance from the terminus is represented by a vector opposite to those representing the other two variables in the redundancy analysis plot (Figure 3). The results from the multivariate analysis therefore suggest that glacier debris cover may host chronosequences similar to those observed in glacier forefields Nicol et al, 2005;Nemergut et al, 2007;Schmidt et al, 2008;Sattin et al, 2009;Schutte et al, 2009Schutte et al, , 2010Philippot et al, 2011;Knelman et al, 2012;Zumsteg et al, 2012).…”
Section: Discussionmentioning
confidence: 62%
“…Particularly, some works suggested that Cyanobacteria are important sources of C in very early succession stages and some surveys did report high abundances of Cyanobacteria in early colonization stages (Nemergut et al, 2007;Schmidt et al, 2008;Zumsteg et al, 2012). On the contrary, other investigations showed low abundances of Cyanobacteria in glacier forefields without any relation between their abundance and soil age Sattin et al, 2009;Goransson et al, 2011;Knelman et al, 2012). Hence, the role of Cyanobacteria in the very early stages of ecosystem development is currently controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total and photoautotrophic cell counts followed this trend, reaching a maximum in well-formed soils in Zone III. Sattin et al (2009) describe a similar observation based on clone libraries during their work on Mendenhall Glacier foreland soils (USA). Counts at sampling points E2 and F2 could have been influenced by significant numbers of edaphic ciliates which control bacterial populations (Mieczan, unpublished).…”
Section: Microbial Community Along Transectmentioning
confidence: 78%
“…For instance, spore-forming Firmicutes -which may be more easily dispersed-are most abundant in the 4 week postburn soils. As well, Betaproteobacteria, which commonly dominate early successional landscapes Sattin et al, 2009) are more abundant at 16 weeks, when the decrease in soil organic matter (Table 1) may select for more oligotrophic taxa. We performed Mantel tests to examine correlations between environmental parameters and community structure.…”
Section: Discussionmentioning
confidence: 99%